Africa's fragmented spaces, intertwined memories and shifting urban identities in a globalized world - (:unkn) unknown (My University, 2024)
Since the 1970s, the dynamics of the globalisation of trade have accelerated considerably thanks to modern communication systems and the circulation of information. In a world that is becoming increasingly interconnected and prey to forms of cultural smoothing, sub-Saharan Africa is emerging as a singular geographical space oscillating between a desire for integration and economic realities characterised by dependence and the exploitation of resources. In this particular context, the continent's cities appear as places that bear witness to a past deeply marked by colonisation (when they are not the pure product of it) and to the profound changes brought about by integration into an increasingly uniform world, while at the same time generating singularities that are expressed, among other things, in urban spaces.
Keywords: African Research